Impact of a gestational exposure to diesel exhaust on offspring gonadal development: experimental study in the rabbit. (18th June 2018) - Bourdon, M.; Torres-Rovira, L.; Monniaux, D.; Faure, C.; Levy, R.; Tarrade, A.; Rousseau-Ralliard, D.; Chavatte-Palmer, P.; Jolivet, G.
Abstract: The aim of the present work was to address experimentally the possible impact of exposure to air pollution during gestation on the differentiation and function of the gonads of the offspring using a rabbit model. Rabbits were exposed daily to diluted diesel exhaust gas or filtered air from the 3rd until the 27th day of gestation, during which time germ cells migrate in genital ridges and divide, and fetal sex is determined. Offspring gonads were collected shortly before birth (28th day of gestation) or after puberty (7.5 months after birth). The structure of the gonads was analyzed by histological and immunohistological methods. Serum concentrations of testosterone and anti-Müllerian hormone were determined using ELISA. The morphology and the endocrine function of the gonads collected just at the arrest of the exposure were similar in polluted and control animals in both sexes. No differences were observed as well in gonads collected after puberty. Sperm was collected at the head of the epididymis in adults. Sperm motility and DNA fragmentation were measured. Among all parameters analyzed, only the sperm DNA fragmentation rate was increased three-fold in exposed males. Mechanisms responsible for these modifications and their physiological consequences are to be further clarified.